Tropical Soda Apple Making a Comeback - Pat Hogue; Jeff Mullahey (EDIS, 2003)
This document is WEC 178, one of a series of the Wildlife Ecology and Conservation Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date: May, 2003.